Pandangan UNCRC Pada Fenomena Anak Jalanan di Kota Mataram - Khairur Rizki; Kurnia Zulhandayani Rizki; YA. Wahyuddin; Ismah Rustam (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2022)
The phenomenon of street children exists in all cities in Indonesia, as well as in the city of Mataram. In this study, authors examine the fulfillment and protection of the human rights of street children in the city of Mataram. The point of view used in this research is using the concept of the International Regime to see the fulfillment and protection of children's rights through the United Nations Convention on the Rights of the Child (UNCRC). The research method uses a qualitative approach and the source of the data obtained is secondary data from literature study by collecting reading sources that are related to the issue. The result of this research is the phenomenon of street children occurs due to economic, educational, social and cultural factors. In addition, the lack of knowledge of laws and regulations also affects the exploitation of children. Other findings also indicate that there are forms of exploitation by certain elements of street children in Mataram. The impact of child exploitation can be in the form of psychological pressure and physical violence that children receive.